(3GdJMhdGJ GdcHQi aj CfXeI eQGbHI GdJSjjQ hGdehGRfGJ GdJbOjQjI (B/s - (3jMjGhj, fYjeIs; (3ebQj, RcjIs ((3YeGf(B: s (3OGQ GdQGjI ddfTQ hGdJhRjY(B, s, 2015)
(3jVe eONd deQGbHI GdJSjjQ, GdCOGA heDTQGJ Jbjje GdCOGA, CSYGQ GdJMhjd GdOGNdj heQGbHI GdJSjjQ HESJYeGd GdehGRfGJ GdJbOjQjI, GdehGRfI GdJbOjQjI ddeHjYGJ , GdehGRfI GdJbOjQjI ddEfJGL hGdehGRfI GdJbOjQjI ddJehjfGJ, GdJhLgGJ GdMOjKI dfXGe GdehGRfGJ GdJbOjQjI, GdCOhGJ GdJbdjOjI aj Jbjje GdCOGA hGdCOhGJ GdMOjKI dJbjje GdCOGA(B. s
(3HHdjhZQGajG(B: (3U(B.373-388s
Keywords: (3GdejRGfjGJ GdJbOjQjIs; (3Jbjje GdCOGAs; (3eQGbHI GdEfJGLs